The sensory-motor theory of rhythm and beat induction 20 years on: a new synthesis and future perspectives - Todd, Neil P.; Lee, Chris S. (Frontiers in Human Neuroscience, 2015)
Some 20 years ago Todd and colleagues proposed that rhythm perception is mediated by the conjunction of a sensory representation of the auditory input and a motor representation of the body (Todd 1994, 1995), and that a sense of motion from sound is mediated by the vestibular system (Todd 1992, 1993). These ideas were developed into a sensory-motor theory of rhythm and beat induction (Todd et al. 1999). A neurological substrate was proposed which might form the biological basis of the theory (Todd et al. 2002). The theory was implemented as a computational model and a number of experiments conducted to test it. In the following time there have been several key developments. One is the demonstration that the vestibular system is primal to rhythm perception, and in related work several experiments have provided further evidence that rhythm perception is body dependent. Another is independent advances in imaging, which have revealed the brain areas associated with both vestibular processing and rhythm perception. A third is the finding that vestibular receptors contribute to auditory evoked potentials (Todd et al. 2014ab). These behavioural and neurobiological developments demand a theoretical overview which could provide a new synthesis over the domain of rhythm perception. In this paper we suggest four propositions as the basis for such a synthesis. (1) Rhythm perception is a form of vestibular perception; (2) Rhythm perception evokes both external and internal guidance of somatotopic representations; (3) A link from the limbic system to the internal guidance pathway mediates the “dance habit”; (4) The vestibular reward mechanism is innate. The new synthesis provides an explanation for a number of phenomena not often considered by rhythm researchers. We discuss these along with possible computational implementations and alternative models and propose a number of new directions for future research.